ANALISIS NILAI KURS RUPIAH DAN NILAI INDONESIA CRUDE PRICE (ICP) SERTA PENGARUHNYA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DITENGAH PEMBERLAKUAN MEA 2015 - -, Febriyanto (Jurnal Manajemen Magister Darmajaya, 2015)
This study aims to identify and analyze the Value Change Value Rupiah and Indonesia Crude Price (ICP) And Its Influence on Stock Price Index (CSPI) amid Enforcement of MEAs 2015. The data used as a sample in this research is data JCI, ICP and Exchange Value rupiah is restricted to the data of late closing of each month during the observation period 2014-2015 year or towards the implementation of the AEC program. Reasons for the selection period of the year is used to get more accurate results in accordance with the current state. This study uses a quantitative method with multiple regression analysis tool to examine the effect of exchange rate and any association between ICP value against JCI. The hypothesis of this study is "Value Exchange and ICP affect the JCI". Based on the calculation, the result that the hypothesis is proven, meaning that when the value of Rupiah and ICP changes the composite index will be affected. The implementation of MEA their situation basically no impact on economic activity significantly. This condition is seen by JCI during the observation period fluctuations in conditions in the range of stable value.Keywords: JCI, Indonesia Crude Price, Value Rupiah, Economy